USE OF TRADITIONAL VETERINARY MEDICINE IN NHEMA COMMUNAL AREA OF THE MIDLANDS PROVINCE, ZIMBABWE - Maroyi, Alfred (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
This study documents the use of ethno-veterinary medicine to treat livestock in Nhema communal area in the Midlands province of Zimbabwe. This study employed oral interviews and detailed discussions with 69 smallholder farmers and 3 traditional healers. The local people use 23 plant species belonging to 16 families as ethno-veterinary remedies. Two plant families were particularly frequent in usage: Fabaceae and Solanaceae, while the most utilized plant species were Aloe chabaudii (UV = 0.69), Aloe greatheadii (UV = 0.65), Adenium multiflorum (UV = 0.63), Vernonia amygdalina (UV = 0.61), Nicotiana tabacum (UV = 56), Solanum lycopersicum (UV = 55), Capsicum annum (UV = 53) and Pouzolzia hypoleuca (UV = 51). Fourteen animal conditions were identified in the surveyed area. The major and most common animal diseases were tick-borne diseases, eye problems, retained afterbirth, fleas, lice and diarrhoea. The majority of ethno-veterinary remedies (78%) were collected from the wild, with respondents mostly using herbs (11 species, 48%), followed by 6 trees (26%), 4 shrubs (17%), and 2 climbers (9%). The most frequently used plant parts were leaves (51%), followed by bark (16%), roots (13%) and fruits (10%). These remedies were mostly administered as decoctions or infusions of single plants. These plants were used not only as alternatives to conventional veterinary drugs but also because in certain diseases they were thought to be more efficacious. In view of many and widespread uses of wild plants as ethno-veterinary remedies, further research into their pharmacological activities may prove worthwhile.